Multispiral Computed Tomography in the Diagnosis of Adrenal Incidentalomas - Yu. V. Shevchenko; P. V. Seliverstov; Yu. A. Privalov (Acta Biomedica Scientifica, 2019)
Many years of experience in identifying patients with various pathologies of the adrenal glands using multispiral computed tomography are presented. Multispiral CT is a highly informative method of choice in the diagnosis of adrenal tumors. Multispiral CT in the perfusion version of the tumor of the adrenal gland increases the accuracy of diagnosis, which optimizes the tactics of treatment. Improving the algorithm for assessing perfusion indices of the adrenal gland incidentalomas using multispiral CT will allow to evaluate the histological nature of the pathological process. It is justified to conduct perfusion MSCT studies in patients with volumetric adrenal masses with the purpose of differential diagnosis of hyperplastic and tumor processes in them. An attempt was made to develop an algorithm for MSCT diagnostics of the adrenal glands and determine its effectiveness. The radiological characteristic of the adrenal glands incidentalomas is a reflection of their morphological structure. There are statistically significant differences in aldosterone-producing and cortisol-producing adenomas in size and CT density. Morphological signs of adrenal tumor degeneration correlate with functional activity. Surgical treatment is absolutely indicated for patients with incidentalomas corresponding to the radiological phenotype of malignant tumors, as well as for patients who have revealed hormonal activity during a comprehensive examination. Dynamic observation is indicatedfor patients with hormonal-inactive incidental small-sized (< 4 cm) in the absence ofradiological signs of malignancy. In patients with an extremely high risk of surgical treatment, endovascular interventions aimed at suppressing adrenal hyperfunction are advisable. The main prognostic factors for adrenal glands incidentalomas are: radiological phenotype, hormonal activity, duration of the disease, the choice of adequate treatment tactics. In surgical treatment, the prognosis depends on the morphological characteristics of adrenal gland incidentalomas.